Medical advisability of softball youth pitching recommendations on the internet - Coden, G.; Akamefula, R. A.; Watters, A.; Ierulli, V.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2024)
Objective Developing softball pitchers are prone to injury due to the repetitive throwing motion. Many children and parents use the internet as a source of medical advice, but this information may not always be aligned with medical guidelines. The purpose of this study was to assess the medical advisability of injury prevention guidelines for developing softball pitchers on websites using Google as the primary search engine.